The Interference of Secular Authority in the Proceedings of Ecumenical Councils from a Historical and Legal Perspective - Kiliszek, Maciej (Prawo Kanoniczne, 2025)
The article examines how historical interferences by secular authority in the proceedings of ecumenical councils contributed to the formation of contemporary norms of canon law, particularly Canon 338 of the 1983 Code of Canon Law. The research problem focuses on the evolution of the councils’ autonomy. The aim of the study is to demonstrate how the Church’s struggle for independence influenced the ultimate codification of papal prerogatives. The historical and legal analysis, which takes into account both procedural and dogmatic aspects, demonstrates that the initial dominance of secular power compelled the Church to gradually establish clear legal principles. Canon 338 of the 1983 Code of Canon Law constitutes the legal culmination of centuries-long efforts to secure the autonomy of councils. At the same time, in light of recent Vatican documents, the study emphasizes that these norms do not represent a definitive conclusion but rather a starting point for contemporary debates on papal primacy in the context of synodality and ecumenical dialogue.